UKURAN PERUSAHAAN, PROFITABILITAS, FINANCIAL LEVERAGE, DIVIDEND PAYOUT RATIO DAN KECENDERUNGAN PERATAAN LABA - Umi Murtini; Aditya Denny O.S (Fakultas Bisnis UKDW, 2012)
This study aims to exmine the effect of firm size, profitability, financial leverage, and dividend payout ratio on income smoothing tendency. The grouping of firms with income smoothing and without income smoothing use eckel index. Using binary logistic regression analysis, results shows that firm size and profitabilitas influence on income smoothing tendency. Meanwhile, financial leverage and dividend payout ratio don’t influence on income smoothing tendency. Keywords: income smoothing, profitabilty, size